#TITLE_ALTERNATIVE# - WIDAYANTI (NIM 10107020); Pembimbing : Dr. Agus Yodi Gunawan, DESCA
Applications of two-dimensional cellular automata have been applied to indus- try or natural science to determine patterns or systems. In this …nal project, simulations using model of hexagonal cellular automata with 13 neighborhood will be used to study the spread of the forest …res. The forest …re spread is aÃ‚Â¤ected by some parameters, namely the rate of …re spread, the in‡uence of the wind and the topography. The simulations show that if the forest is ‡at and there is no wind, the …re front spread circularly. Moreover, if the forest is not ‡at and there is wind condition, the …re will spread faster from lower neighborhood height.